Exploring the Currency Swap Agreement: A Deeper Analysis of Sino-Nigerian Relations - Okpevra, Uwomano Benjamin; Eborka, Nkechi Faith (Master Program of Sociology, Universitas Malikussaleh,, 2025)
This study investigates the China-Nigeria Currency Exchange Agreement, a landmark financial arrangement signed in April 2018 aimed at enhancing bilateral trade and investment by allowing transactions in local currencies—Chinese yuan and Nigerian naira—without reliance on the U.S. dollar. The research delves into the agreement’s key objectives, mechanisms of implementation, and its broader implications for trade relations, economic stability, and foreign exchange dynamics between the two countries. Utilizing secondary data sources and a qualitative analytical approach, the study assesses the extent to which the agreement has succeeded in mitigating currency volatility, reducing transaction costs, and strengthening financial autonomy. Furthermore, it explores how such currency swap arrangements can reshape global financial interactions, particularly for emerging economies seeking to diversify their external economic engagements and reduce dependence on dominant currencies like the U.S. dollar. The findings contribute to the growing discourse on South-South cooperation and offer insights into the strategic use of bilateral financial instruments within an increasingly multipolar international economic system.